Acute Rheumatic Fever and Kawasaki Disease Occurring in a Single Patient - Iio, Kazuki; Fukushima, Naoya; Akamine, Keiji; Uda, Kazuhiro; Hataya, Hiroshi; Miura, Masaru (Frontiers in Pediatrics, 2020)
Kawasaki disease and acute rheumatic fever are two major causes of acquired heart disease in the pediatric population. Although both conditions are well-known entities, the association between them has never been described. We report herein a case of 6-year-old male patient who first presented with Kawasaki shock syndrome, followed by acute rheumatic fever one year later. This case implies that the susceptibility to two diseases can coexist in a single patient. In contrast to the prompt intervention given for atypical Kawasaki disease, in the present case the diagnosis was significantly delayed during the otherwise typical presentation of acute rheumatic fever. Our case highlights the difficulty experienced by many pediatricians in developed nations in diagnosing acute rheumatic fever due to its comparative rarity. To prevent diagnostic errors, all pediatricians should be alert to the possibility of acute rheumatic fever even if they are practicing in areas where it is not endemic.